A Survey on Block Chain Based Big Data Storage Security using Encryption Method - Thangaraj, M.; Vinodhini, S. (Journal of Neonatal Surgery, 2025)
Blockchain-based security practices for bigdataentail block chain technology to store and manage massive amounts of data. It protects data integrity, accessibility and confidentiality by employing cryptographic techniques and decentralized networks. This survey explores the integration of blockchain technology with encryption methods to enhance the security of big data storage systems. As the volume and complexity of data grow, traditional security measures often fall short in addressing the unique challenges posed by big data environments. Blockchain offers a decentralized and immutable framework, ensuring data integrity and transparency. The paper categorizes prevalent encryption techniques, including symmetric and asymmetric encryption, homomorphic encryption, attribute-based encryption, and searchable encryption, evaluating their effectiveness in ensuring data confidentiality, integrity, and accessibility. Furthermore, the survey examines the integration of these encryption methods within cloud infrastructures, highlighting the importance of key management, access control, and compliance with data protection regulations. By synthesizing current research and practical implementations, this study aims to provide insights into the strengths and limitations of various encryption strategies, offering guidance for organizations seeking to enhance the security of their big data storage solutions